Length-weight relationship of 37 fish species from the Taquari River (Paranapanema Basin, Brazil) - Nobile, A. B. [UNESP]; Brambilla, E. M. [UNESP]; Lima, F. P. de [UNESP]; Freitas-Souza, D. [UNESP]; Bayona-Perez, I. L. [UNESP]; Carvalho, E. D. [UNESP] (Wiley-Blackwell, 2015)
This work describes the length-weight relationship (LWR) of 37 fish species from the Taquari River, one of the tributaries of the Jurumirim Reservoir in the high Paranapanema Basin, SAo Paulo, Brazil. Information was not yet available in FishBase on LWRs of 22 of the fish species and maximum weights (Wt) of 24 of the fish species. New maximum standard lengths are presented for nine species as well as weights for two fish species.